Electronic modulation of non-van der Waals 2D electrocatalysts for efficient energy conversion - Wang, Hao (2022)
The exploration of efficient electrocatalysts for energy conversion is important for green energy development. Owing to their high surface areas and unusual electronic structure, 2D electrocatalysts have attracted increasing interest. Among them, non-van der Waals (non-vdW) 2D materials with numerous chemical bonds in all three dimensions and novel chemical and electronic properties beyond those of vdW 2D materials have been studied increasingly over the past decades. Herein, the progress of non-vdW 2D electrocatalysts is critically reviewed, with a special emphasis on electronic structure modulation. Strategies for heteroatom doping, vacancy engineering, pore creation, alloying, and heterostructure engineering are analyzed for tuning electronic structures and achieving intrinsically enhanced electrocatalytic performances. Lastly, a roadmap for the future development of non-vdW 2D electrocatalysts is provided from material, mechanism, and performance viewpoints.